Cognition and chronic pain: an analysis on community-dwelling elderly caregivers and non-caregivers - Marielli TERASSI; Ana Carolina OTTAVIANI; Érica Nestor de SOUZA; Francisco José FRAGA; Pedro MONTOYA; Sofia Cristina Iost PAVARINI; Priscilla HORTENSE (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: In recent years there has been an increasing number of elderly people who care for another elderly person in the same household. These elderly people are more susceptible to overload and the presence of chronic pain, while pain can negatively influence cognitive variables. Objective: To compare the performance and cognitive processing of elderly caregivers and non-caregivers with and without chronic pain. Methods: This was a cross-sectional study carried out among 149 elderly people divided into four groups that were matched according to sex, age and schooling. The tests used were a numerical pain assessment scale, the Brief Cognitive Screening Battery (BCSB), Addenbrooke’s Cognitive Examination (ACER-R) and cognitive processing through event-related potentials (P300). Results: Statistically significant differences between participants with and without chronic pain were found with regard to attention/orientation (p=0.045) and visual-spatial skills (p=0.017), and in the total score (p=0.033). In the pain-free group, the caregivers showed better results than the non-caregivers. There were no effects between subjects or interactions (caregiving and pain factors) either on P300 amplitude or on P300 latency. Conclusion: In general, it was observed that pain-free individuals presented better performance. No relationship was observed between the factors care and pain regarding cognitive performance.